2010
DOI: 10.1016/j.neuropharm.2010.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Diarylamidines: High potency inhibitors of acid-sensing ion channels

Abstract: Acid-sensing ion channels (ASICs) are proton-gated cation channels that are predominantly expressed in the nervous system. ASICs are involved in a number of neurological diseases such as pain, ischemic stroke and multiple sclerosis but limited tools are available to target these channels and provide probes for their physiological functions. Here we report that the anti-protozoal diarylamidines, 4′,6-diamidino-2-phenylindole (DAPI), diminazene, hydroxystilbamidine (HSB) and pentamidine potently inhibit ASIC cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
117
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(129 citation statements)
references
References 38 publications
(63 reference statements)
11
117
1
Order By: Relevance
“…DAPI is a diarylamidine, a class of drugs that have been recently shown to block ASIC Na + currents in cultured mice hippocampal neurons, but do not block other epithelial Na + channels, such as ENaCs (Chen et al, 2010). Recently, DAPI has also been demonstrated to inhibit Na + uptake in rainbow trout exposed to ultra-low ionic strength/low pH water (Dymowska et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DAPI is a diarylamidine, a class of drugs that have been recently shown to block ASIC Na + currents in cultured mice hippocampal neurons, but do not block other epithelial Na + channels, such as ENaCs (Chen et al, 2010). Recently, DAPI has also been demonstrated to inhibit Na + uptake in rainbow trout exposed to ultra-low ionic strength/low pH water (Dymowska et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether DAPI, an ASIC selective inhibitor (Chen et al, 2010) displayed a similar dose-response inhibition effect on Na + uptake in zebrafish to that of rainbow trout, flux experiments using 22 Na + were performed on adult zebrafish exposed to low-Na + medium (∼500 µmol l −1 Na + ; Table 1). After 90 min, zebrafish showed reduced Na + uptake with increasing concentrations of DAPI (Fig.…”
Section: Pharmacological Inhibition Of Na + Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…This is in good agreement with our data showing that the toxin/palm contact is determinant to explain inhibition of the peak current or stimulation when this interaction is modified. Domain P has also been proposed to constitute part of the binding site of diarylamidines, which are inhibitors of ASICs (36).…”
Section: The Finger/palm/␤-ball Connecting Domain (Domain P) and The mentioning
confidence: 99%
“…The application of aromatic diamidines is not limited to anti-parasitics. Recently, it was found that aromatic diamidines such as pentamidine, hydroxystilbamidine, and diminazene potently block ASICs [305]. Each of these compounds inhibited ASIC currents, indicating that the linker in each of these diamidines can be variable, while the amidine group linked with an aromatic moiety appears to be essential.…”
Section: Diaminazenementioning
confidence: 99%